Consumer perception on green products of Warung Seni towards purchase intention among young tourists / Annabelle Ambrews and Muhammad Nur Faiz Amran - Ambrews, Annabelle; Amran, Muhammad Nur Faiz (Faculty of Business and Management, 2014)
The environment is a combination of many elements, both living and non-living that make up the surroundings. Some include natural elements and some are manufactured. An environment is all of the conditions, circumstances, etc. that surround and influence life on earth, including atmospheric conditions, food chains, and the water cycle.Thus, the environment is the surrounding that includes living as well as non-living things. The non-living components like land, water, air, temperature etc. influence how animals, plants and we as human beings live in a particular area. Going green may be varying according to the person itself. Some people are extreme purists and green lifestyle is entrenched in everything they do, while others see green as a specific more focused area such as the environment or healthy lifestyles. The iron curtain or resistance to going green exists because nobody is sure exactly what green really means,which leave it open to anyone’s interpretation.While it used to be a colour, now it has a different meaning. Some people limit it to the environment while others look at the entire depth of green activities and global changes. For instance, the government may see it as a policy or paper that is researched and discussed by the correct authorities. Only then can a green policy come into effect and it is usually about a sustainable practice or environmental impact/change.For businesses, they always had the term green as the colour of money, but there is also a sustainable business approach that institutes policies and products that meet current needs without compromising the integrity of the future. Industry often sees it as an obstacle to keep the public happy, so it is defined as regulations that are put in place to protect the environment and people. But for a customer, the definition is mindful of the environment and obligations to protect.